G2C Communication Through Government Service Portals: An Assessment of Kenya’s e-Citizen and eFNS Portals - Robert Aswani, Daniel; Ndanu Mutua, Sylvia (Multidisciplinary Journal of Technical University of Mombasa, 2023)
The automation of government services as exemplified through service portals has increased in a post-COVID-19 world that yearns for social and physical interaction. Although governments have benefitted from an arm’s length service delivery model, consumers of these services expect continuous communication from their governments. Government-to-consumer (G2C) communication is hinged on the fact that consumer (citizens and foreign nationals) engagement has a significant place in the provision of government services and government communication literature posits the place of strategic communication with consumers. While preliminary research suggests the popular usage of government service portals to enhance G2C communication, little is known about the effectiveness and interactivity of G2C communication between the government and consumers of government services. Questions thus abound on the kind of perceptions that consumers have regarding the comprehensiveness, effectiveness, and efficiency of G2C communication through government service portals. In Kenya, the automation of immigration services encapsulated in the e-citizen and e-foreign nationals service (eFNS) portals, offers prudential lessons to concretize and improve G2C communication in a post-pandemic world. This study focuses on communication through the portals between the government and citizens (applying for passports) and foreign nationals (applying for visas, permits, passes, and long-term residences). The study adopted secondary research analysis coupled with interviews carried out with 16 participants: 10 citizens and foreigners; and 6 Ministry of Interior officials. Thematic analysis revealed that automation orients government officials to a generic messaging model that bespeaks incommunicado and frustrates the attainment of effective G2C communication. Additionally, the study established that whereas government officials were endeared to generic communicative incentives of the portals, consumers craved more information and communication from the government through the portals. From the findings, it is indicative that there is an urgent need to re-engineer the portals and institute a communication avenue. There is a need for the avenue to be run by a competent team of communication practitioners that will engage consumers in two-way symmetrical communication if the government is to make use of service portals in an automated post-pandemic world.